Offentlig upphandling av ekologiskt producerade livsmedel - Sundling, Emma Dahlberg (2007)
The Swedish public procurement correspond to approximately 400 milliard Swedish crowns every year which corresponds to about a fourth of the Swedish Gross National Product. Setting proper demands in the procurement is a useful tool to drive the development towards more environmentally adapted products and provisions. The Act on Public Procurement (Lagen om offentlig upphandling, 1992:1528) gives the municipalities opportunities to consider environmental properties during the procurement. This combined literature and empirical study investigates the experiences made by the three municipalities Ludvika, Borlänge and Smedjebacken during the process of certifying their school kitchens as organic in cooperation with KRAV. The main conclusion is that without compassion and curiosity for developing a green public procurement changes can be hard to implement. A political support within the municipality is important for carrying out new ideas and realising the changes necessary. According to this study factors contributing to keeping the budget has been; seasonally adapted ingredients and menus for the school meals, changing the eating habits towards less meat-based meals and inserting greater volumes organically produced foods in the procurement agreement. Another finding in this study is that the cooperative scheme of many years' standing between these three municipalities has been a successful way of spreading information and experiences as well as building commitment and environmental awareness during the certifying process.